Go Online! Reconfiguring Writing Courses for the New, Virtual World - Gray-Rosendale, Laura; Rosendale, Steven (Peter Lang International Academic Publishers, 2022)
COVID-19's impacts revealed that teaching writing online was no longer merely an issue of convenience or economic necessity-it was critical to public health and equity concerns as well. Now higher education faces one of its greatest historical challenges, expanding online offerings to fully engage and support students around the world. Gathering together educators who teach writing at college and graduate levels using creative hybrid, blended, and online/remote/virtual modes, this book should be required reading for all teachers and administrators. The volume features those new to online teaching alongside experienced online writing teachers. Referencing the latest research in online teaching and writing, contributors share stories of crucial successes as well as unforeseen difficulties. Essays address compelling concerns such as engaging diversity and cultural inclusivity, social justice, as well as global learning in online writing courses; radically reshaping graduate seminars for online delivery; flipping classrooms to promote more successful writing instruction; fostering greater community within online writing classrooms; examining the problems and possibilities of Learning Management Systems for teaching writing; sustaining remote writing-centered archival research; avoiding Zoom fatigue in writing classes by using design thinking; utilizing expressive arts in online writing classes; mentoring doctoral students online; constructing meaningful approaches to online peer writing feedback; as well as making access and inclusivity central to online writing course design.